Comparative Impact of Integrated Palliative Care vs. Standard Care on the Quality of Life in Cancer Patients: A Global Systematic Review and Meta-Analysis of Randomized Controlled Trials. - Addisu Getie; Afework Edmealem; Tegene Atamenta Kitaw (PLoS ONE)
IntroductionCancer is a leading cause of global morbidity and mortality, significantly impairing patients' quality of life (QoL). Integrated Palliative Care (IPC) has been proposed as a holistic approach to enhance quality of life by addressing patients' physical, emotional, and psychosocial needs. While some studies suggest Integrated Palliative Care improves quality of life more than standard care, the evidence remains inconclusive. This systematic review and meta-analysis aim to evaluate the comparative impact of Integrated Palliative Care versus standard care on the quality of life in cancer patients. MethodsA comprehensive search of databases including PubMed, Cochrane Library, and Embase was conducted. We selected randomized controlled trials (RCTs) comparing Integrated Palliative Care and standard care for cancer patients, focusing on the quality of life as measured by validated tools such as the EORTC QLQ-C30 and FACT-G. Data were pooled using a random-effects model to account for study heterogeneity. Subgroup and sensitivity analyses were also performed. ResultsNine randomized controlled trials involving 1,794 patients met the inclusion criteria. Meta-analysis showed that Integrated Palliative Care significantly improved quality of life compared to standard care (SMD = 3.25; 95% CI: 1.20-5.30; p < 0.001). Studies conducted in Asia showed the highest standardized mean difference (SMD = 6.15; 95% CI: 3.07-9.23; p < 0.001), followed closely by studies from Africa (SMD = 6.0; 95% CI: 5.13-6.87; p < 0.001), compared to those from other regions. Similarly, research focusing on lung cancer patients showed the greatest standardized mean difference of (SMD = 6.15; 95% CI: 3.07-9.23; p < 0.001) relative to other cancer types. Furthermore, studies involving newly diagnosed cancer patients recorded the highest standardized mean difference of (SMD = 5.69; 95% CI: 4.57-6.80; p < 0.001). ConclusionIntegrated Palliative Care significantly enhances the quality of life in cancer patients compared to standard care. These findings support integrating Integrated Palliative Care into oncology practices to provide comprehensive, patient-centered care that addresses both physical and emotional needs. Further research should explore long-term benefits across diverse populations.